Advanced throughput analytical strategies for the comprehensive HRMS screening of organic micropollutants in eggs of different bird species. (January 2023) - Gkotsis, Georgios; Nika, Maria-Christina; Athanasopoulou, Antonia I.; Vasilatos, Konstantinos; Alygizakis, Nikiforos; Boschert, Martin; Osterauer, Raphaela; Höpker, Kai-Achim; Thomaidis, Nikolaos S.
Abstract: Raptors are ideal indicators for biomonitoring studies using wildlife in order to assess the environmental pollution in the terrestrial ecosystem, since they are placed in the highest trophic position in the food webs and their life expectancy is relatively long. In this study, 26 eggs of 4 bird species (Peregrine falcon, Eurasian curlew, Little owl and Eagle owl) collected in Germany, were investigated for the presence of persistent organic pollutants (POPs) and thousands of contaminants of emerging concern (CECs). Generic sample preparation protocols were followed for the extraction of the analytes and the purification of the extracts, and the samples were analyzed both by liquid (LC) and gas chromatography (GC) coupled to high resolution mass spectrometry (HRMS), for capturing a wide range of organic micropollutants with different physicochemical properties. State-of-the-art screening methodologies were applied in the acquired HRMS data, including wide-scope target analysis of 2448 known pollutants and suspect screening of over 65, 000 environmentally relevant compounds. Overall, 58 pollutants from different chemical classes, such as plant protection products, per- and polyfluoroalkyl substances and medicinal products, as well as their transformation products, were determined through target analysis. Most of the detected compounds were lipophilic (logP>2), although the presence of (semi)polar contaminants should not be overlooked, underlying the need for holistic analytical approaches in environmental monitoring studies. p, p'-DDE, PCB 153 and PCB138, PFOS and methylparaben were the most frequently detected compounds. 50 additional substances were identified and semi-quantified through suspect screening workflows, including mainly compounds of industrial use with high production volume. Graphical abstract: Image 1 Highlights: 26 eggs of Peregrine falcon, Eurasian curlew, Little and Eagle owl were analyzed. 58 organic pollutants were determined by LC- and GC-HRMS wide-scope target analysis. Highest frequency and concentration levels were observed for lipophilic compounds. PFOS was the most frequent and abundant compound among 13 detected PFAS. 50 substances were identified and semi-quantified through suspect screening.